Formal methods for semi-autonomous driving - Seshia, Sanjit A.; Sadigh, Dorsa; Sastry, S. Shankar (Proceedings - ACM IEEE Design Automation Conference, 2015)
We give an overview of the main challenges in the specification, design, and verification of human cyber-physical systems, with a special focus on semi-autonomous vehicles. We identify unique characteristics of formal modeling, specification, verification and synthesis in this domain. Some initial results and design principles are presented along with directions for future work.